Impoliteness Strategies in Online Political Discourse: A Study of Hate Comments on Ahmad Sahroni’s Instagram Account - Lubis, Delfi Nazilah; Siagian, Theofani Leonita; Tantira, Nikita; Sibarani, Lydia Permata Sari; Rangkuti, Rahmadsyah (Universitas Muhammadiyah Mataram, 2025)
Language used in digital communication shows how people express feelings and deal with social power. In the case of Indonesia’s social media, being rude or impolite has become a big part of how users share their opinions and criticize others. This study looks into the different ways people use impolite language in comments that target Ahmad Sahroni, an Indonesian lawmaker, on Instagram. This research collected 50 comments from various Instagram posts, including political and lifestyle topics, to cover a wide range of online hostility. This study uses a qualitative descriptive method and applies Computer Mediated Discourse Analysis (CMDA) to understand how social media features influence the way people talk. Culpeper’s Impoliteness Theory is used as the main way to analyze the language. The results show five main types of impolite strategies: bald on record, positive impoliteness, negative impoliteness, sarcasm or mock politeness, and withholding politeness. Among those, positive impoliteness is the most common. People often use moral and religious words to make their comments seem justified, while humor and sarcasm help hide their anger. These findings show that impolite language isn’t just about showing moral judgment in online conversations. This study adds to the understanding of how language works in digital spaces by looking at impoliteness in moral contexts and helps explain how social media supports group behavior around moral responsibility